Structure and dynamics of Trichoderma harzianum Cel7B suggest molecular architecture adaptations required for a wide spectrum of activities on plant cell wall polysaccharides - Sonoda, Milton T.; Godoy, Andre S.; Pellegrini, Vanessa O.A.; Kadowaki, Marco A.S.; Nascimento, Alessandro S.; Polikarpov, Igor (Biochimica et biophysica acta. General subjects, 2019)
Cellulases from glycoside hydrolase family 7 (GH7) play crucial roles in plant lignocellulose deconstruction by fungi, but structural information available for GH7 fungal endoglucanases is limited when compared to the number of known sequences in the family. Here, we report the X-ray structure of the glycosylated catalytic domain (CD) of Trichoderma harzianum endoglucanase, ThCel7B, solved and refined at 2.9 Å resolution. Additionally, our extensive molecular dynamics simulations of this enzyme in complex with a variety of oligosaccharides provide a better understanding of its promiscuous hydrolytic activities on plant cell wall polysaccharides. The simulations demonstrate the importance of the hydrogen bond between substrate O2 hydroxyl in the subsite −1 and a side chain of catalytic Glu196 which renders ThCel7B capable to catalytically cleave cello and xylooligosaccharides, but not mannooligosaccharides. Moreover, detailed structural analyses and MD simulations revealed an additional binding pocket, suitable for accommodation of oligosaccharide decorations and/or substrates with mixed glycoside bonds that abuts onto the binding cleft close to subsite +2. [Display omitted] •The crystal structure of Trichoderma harzianum endoglucanase Cel7B was determined and refined at 2.9 Å resolution.•A N-linked glycan was found docked into the enzyme active site, mimicking the hydrolysis product.•Molecular dynamics (MD) simulations confirmed the binding mode for substrates at subsites −2 to +2.•MD simulations also revealed an unidentified pocket that could accommodate decorations at subsite +2.•The interactions with oligosaccharides provided a rationale for the selectivity for gluco and xylooligosaccharides.